Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions

No, Mac. @mcfizzy321

u can write the 2nd equation as
y = 20 - 8x

as y = x^2 - 2x + 4
and y = 20 - 8x
so
x^2 - 2x + 4 = 20 - 8x
proceed

So, would combine x2 and 2x and then continue with simplifying?

\[x^2 - 2x + 4 = 20 - 8x\]
\[x^2 + 6x - 16 = 0\]
solve the equation

Okay, so the factors would be (x-8)(x+2)... is this right so far?

it would be (x + 8)(x - 2)

Okay, got it. Is this it, or is there more to do? Sorry, I was so confused on this one.

I'm wondering... how do we find (84,4) ?

I have no idea, that's what I was confused about too.

because (x+8)(x-2) we have x = -8, 2 ... plug them in and solve for y?!

wait I think so... like if x = 2
8(2) + y = 20
16+y=20
y=20-16 = 4

duh I was getting there k...

Ahhhh lol. Makes sense!

So, it would be B?

Okay, so C?

yes

Thank you so much!!!!